Development of HOTS-Based Cognitive Assessment Instruments to Train Students' Critical Thinking Skills - Rukmana, Musma; Maulidiah, Maulidiah; Kurniahtunnisa, Kurniahtunnisa; Utami, Aisyiah Restutiningsih Putri (Biopedagogia, 2024)
Critical thinking skills are very important for students in the 21st century. The development of HOTS-based cognitive assessment instruments aims to produce assessment instruments that are valid, practical, and effective evaluation tools. This development research modified Thiagarajan's 4-D model with stages: define, design, develop, and disseminate. After revision and approval by experts, the instrument design draft was analyzed. After that, a limited test was carried out on a total of 34 students in class XI Science 1 at SMA Negeri 9 Pangkep. Tests, questionnaires, interviews, and observations were the methods used in data collection. The research results showed that: (1) the validity of the HOTS-based cognitive assessment instrument was in the very valid category with a score of 93.33% from the media aspect and 92% from the material aspect; (2) the assessment instrument developed was in the very practical category which was obtained from the results of student responses with a percentage of 82.35% and teacher responses with a percentage of 88%; and (3) the effectiveness of the instrument was in the effective category obtained from test data on student learning outcomes of 73.52% in the effective category, and students' critical thinking abilities were on average in the good category. Based on the results obtained, a conclusion was drawn that the HOTS-based cognitive assessment instrument meets the criteria for validity, practicality, and effectiveness.